1984
DOI: 10.1159/000242030
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acids and Glucose Levels in the Rat Fetus and Dam after Chronic Maternal Alcohol Consumption

Abstract: To evaluate the effect of chronic maternal alcohol consumption on plasma amino acid and glucose levels in both the fetus and the mother, female Sprague-Dawley rats were divided into 3 dietary treatment groups. Group 1 (alcohol) was fed ad libitum a stock diet plus 20% alcohol in drinking water for at least 4 weeks before mating and 30% alcohol during gestation. Group 2 was pair-fed the stock diet plus corn starch calorically equivalent to the amount of alcohol consumed by group 1 animals. Group 3 (control) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 9 publications
(14 reference statements)
3
7
0
Order By: Relevance
“…A final acute challenge of ethanol or acidemia following the chronic exposure resulted in a significant reduction of glutamine, arginine, citrulline, asparagine, serine, threonine, tryptophan, methionine, leucine, histidine, tyrosine, valine, and isoleucine, compared with that at baseline, while glutamate was elevated. Glucose, in contrast, was not altered in response to ethanol, a finding that is consistent with previous reports; maternal ethanol consumption reduces fetal, but not maternal plasma glucose levels (Falconer, 1990; Marquis et al, 1984; Richardson et al, 1985). Utilizing a chronic, but not a binge ethanol exposure during the first two trimester-equivalents of human brain growth in rats, Karl and coworkers (Karl et al, 1995) found increased fetal glutamate levels, but glutamine was not altered in the mother or the fetus.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A final acute challenge of ethanol or acidemia following the chronic exposure resulted in a significant reduction of glutamine, arginine, citrulline, asparagine, serine, threonine, tryptophan, methionine, leucine, histidine, tyrosine, valine, and isoleucine, compared with that at baseline, while glutamate was elevated. Glucose, in contrast, was not altered in response to ethanol, a finding that is consistent with previous reports; maternal ethanol consumption reduces fetal, but not maternal plasma glucose levels (Falconer, 1990; Marquis et al, 1984; Richardson et al, 1985). Utilizing a chronic, but not a binge ethanol exposure during the first two trimester-equivalents of human brain growth in rats, Karl and coworkers (Karl et al, 1995) found increased fetal glutamate levels, but glutamine was not altered in the mother or the fetus.…”
Section: Discussionsupporting
confidence: 92%
“…Utilizing a chronic, but not a binge ethanol exposure during the first two trimester-equivalents of human brain growth in rats, Karl and coworkers (Karl et al, 1995) found increased fetal glutamate levels, but glutamine was not altered in the mother or the fetus. Other rat studies involving a similar exposure paradigm have demonstrated a decrease in maternal plasma proline levels (Marquis et al, 1984), as well as reduced sodium dependent intestinal absorption of methionine (Polache et al, 1996), and taurine (Martin-Algarra et al, 1998). In contrast to these chronic exposure studies, an acute ethanol study in the pregnant mouse resulted in a significant reduction in the plasma concentrations of several amino acids, including threonine, serine, glutamine, glycine, alanine, and methionine (Padmanabhan et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maternal plasma concentrations of threonine, serine, glutamine, glycine, alanine, and methionine were reduced in response to acute alcohol exposure in the mouse (Padmanabhan et al 2002) and chronic alcohol exposure in the rat reduced maternal plasma proline concentrations (Marquis et al 1984) and increased fetal plasma glutamate concentrations (Karl et al 1995). These findings characterize the effect of alcohol on maternal amino acids, while there is a paucity of information on the effect to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the level of most amino acids is considerably higher in fetal than in maternal blood (14)(15)(16). Tryptophan, as well as total amino acid concentration, in plasma decreases significantly with pregnancy (16) while in the fetus (2 1 days) the plasma tryptophan level is higher (65-91%) than in the mother (16,17). This suggests that the plasma tryptophan level in the fetus may already be high so that an additional elevation via the maternal ingestion of tryptophan may not have a further stimulatory effect.…”
Section: Methodsmentioning
confidence: 99%